(untitled) (Journal of Enam Medical College, 2015)
Spontaneous coronary artery dissection is an extremely rare cause of acute coronary syndrome. Although it predominantly affects young women in the peripartum period, it can also occur in men. The left coronary artery is most frequently involved. The usual presentation is ST segment elevation myocardial infarction. Although several treatment modalities have been proposed, the optimal treatment options still remain to be established. This current case report focuses on a 40- year-old male presented with acute coronary syndrome and subsequently was found to have coronary artery dissection. DOI: http://dx.doi.org/10.3329/jemc.v5i1.21498 J Enam Med Col 2015; 5(1): 52-57